Strategies For Defending The Yellow Islamic Classic Book Tradition in Madrasah Al Washliyah - Harahap, Muhammad Riduan; Lubis, M Syukri Azwar (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This paper aims to discuss In an era of dynamic globalization and rapid changes in educational paradigms, educational institutions around the world are faced with the challenge of revising and modernizing their methods and curricula. This context also applies to Madrasah Al Washliyah which has a deep tradition of teaching the YellowIslamic classic Book. This paper explores how Madrasah Al Washliyah maintains the essence of the Kitab Kuning tradition while remaining relevant amidst the evolution of global education. Using a qualitative approach, the study uncovers the various techniques, innovations, and strategic measures implemented by the madrasah in combining traditional and contemporary methods. The main finding of this study is the application of hybrid methods in the teaching of the Kitab Kuning by Madrasah Al Washliyah. It is also found that community support, active participation of alumni, as well as the madrasah's ability to adapt the content and teaching approach to the needs of the younger generation, play a vital role in the sustainability of this tradition. This study offers a valuable perspective for other educational institutions that seek to blend tradition with the demands of modernity in the current era.